Novel light treatment for digital ulcers in systemic sclerosis: a feasibility study. (23rd February 2017) - Hughes, Michael; Moore, Tonia; Manning, Joanne; Wilkinson, Jack; Watson, Stuart; Samraj, Prawin; Dinsdale, Graham; Roberts, Chris; Herrick, Ariane; Murray, Andrea
Abstract: Background: Locally acting, well-tolerated treatments for digital ulcers in patients with systemic sclerosis are needed. We aimed to investigate the safety, feasibility, and tolerability of a novel light treatment, and to tentatively assess treatment efficacy. Methods: Light treatment with an in-house built phototherapy lamp was administered twice per week for 3 weeks, with follow-up at 4 and 8 weeks. Adverse events were documented. Data on patient opinion about the time to deliver, feasibility ("not feasible", "indifferent", "feasible"), and pain (visual analogue scale [VAS], 0–100) were collected. Patient and clinician assessment of severity of digital ulcers (VAS, 0–100) was documented. An independent assessor graded change in appearance of digital ulcers from photographs (−2 to +2). Laser doppler imaging (to assess perfusion) was performed before and after treatment. A linear mixed-effects model was used to assess change in digital ulcer status. This study is registered withClinicalTrials.gov, numberNCT02472743 . Findings: Eight patients with 14 digital ulcers were recruited. 46 light treatments were administered, with no adverse events. All patients believed that light treatment was "feasible" and "took just the right amount of time", with a low associated mean pain VAS of 1·6 (SD 5·2). Severity of digital ulcers as judged by patients and clinicians improved during the study (mean change in VAS −7·1 and −5·2, respectively; both p≤0·001). According to independent assessment, mean change in appearance of digital ulcers per week was 0·14 (95% CI 0·0–0·3) (p=0·01). There was a significant increase in the relative (compared with baseline) mean perfusion after (compared with before) light treatment, in particular at the centre of the digital ulcer (0·32, 95% CI 0·13–0·52; p=0·0013). Interpretation: Light treatment for digital ulcers in systemic sclerosis is safe, feasible, and well tolerated. There was an early tentative suggestion of treatment efficacy. Future research is warranted to develop light-based treatment as a locally acting therapy for digital ulcers in patients with systemic sclerosis. Funding: Arthritis Research UK.